Numerical Simulation of Thermal Energy Storage in Underground Soil Heat Accumulator - Kortiš Ján; Gottwald Michal (Civil and Environmental Engineering, 2014)
The alternative energy sources have been getting popular for last decades as a new way to obtain enough energy especially for countries which do not have rich natural reservoirs of fossil fuels. Gathering the thermal energy from the solar radiation seems to be as one of the cheapest alternatives of them. The disadvantage of it is the overflow of the heat energy during the summer and lack of them during the winter, when the demand for heat is on top. The underground thermal energy storage can be a good alternative for accumulating the heat energy and then offers it on demand. However, it is difficult to monitor the real physical condition in the soil. In the article, the results of numerical simulation are shown as a good way for a better identification of the process of accumulating the energy to the soil material.